Prevalence and factors associated with puerperal sepsis among postnatal women at a Tertiary Referral Hospital in Western Uganda - Brenda Nabawanuka; Moses Asiimwe; Pauline Irumba; Julian Aryampa; George Wasswa; Michael Muhoozi; Peterson Amumpaire; Joy Acen; Shamim Katusabe; Joan Tusabe; Joshua Epuitai (PLoS ONE, 2025)
Background Puerperal sepsis remains one of the leading causes of maternal mortality and morbidity in Uganda. Aim This study assessed the prevalence and factors associated with puerperal sepsis among postpartum women at Fort portal Regional Referral Hospital located in western Uganda. Methods A cross-sectional design was employed in the study. We conducted a records review of the patient files of 180 postnatal mothers who were admitted at Fort Portal Regional Referral Hospital from 20 February, 2024 to 01 April, 2024. A data abstraction checklist was used to collect data from participant files based on strict inclusion and exclusion criteria. Data was entered in Microsoft Excel and exported to STATA17 for data analysis. Descriptive analysis and logistic regression analysis were performed to determine the prevalence of puerperal sepsis and determinants. Bivariate and multivariate logistic regression analysis was conducted for significant factors presented as Adjusted Odds Ratios (aOR) at p ≤ 0.05. Results The median age of participants was 25.5 years (1QR = 20−30) and the majority (77%) had primary education. The prevalence of postnatal sepsis was 24%. Duration of hospital stay [aOR=2.30; 95%CI (1.552–3.398); p=<0.001], history of antepartum hemorrhage [aOR=29.09; 95% CI (1.182–716.38); p = 0.039] and Anemia [aOR=0.01; 95% CI (0.001–0.218); p = 0.004] were identified as factors associated with puerperal sepsis among postnatal women upon multivariate logistic regression. Conclusion Puerperal sepsis was common in our setting. This study found that mode of delivery, duration of hospital stay, anemia, and Antepartum hemorrhage, were the determining factors contributing to puerperal sepsis, infection prevention measures during cesarean sections, and reducing the length of hospital stay would prove to be beneficial in the prevention of sepsis.